2018
DOI: 10.1016/j.drudis.2018.01.022
|View full text |Cite|
|
Sign up to set email alerts
|

NCp7: targeting a multitask protein for next-generation anti-HIV drug development part 2. Noncovalent inhibitors and nucleic acid binders

Abstract: Nucleocapsid protein 7 (NCp7) represents a viable target not yet reached by the currently available antiretrovirals. It is a small and highly basic protein, which is essential for multiple stages of the viral replicative cycle, with its structure preserved in all viral strains, including clinical isolates. NCp7 can be inhibited covalently, noncovalently and by shielding the nucleic acid (NA) substrates of its chaperone activity. Although covalent NCp7 inhibitors have already been detailed in the first part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…Notably, many studies have shown the potential applications of selenium compounds for the treatment of infectious diseases. The antimicrobial efficacy of selenium compounds has been tested against a great variety of microorganisms, demonstrating their activity as antibacterial [ 22 ], antifungal [ 23 ], antiviral [ 24 ] and antiparasitic agents [ 25 ]. Ebselen ( 1 ) is the most well-known and well-studied seleno-derivative, especially for its antioxidant effects, GPx-like activity [ 26 ] and antimicrobial activity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, many studies have shown the potential applications of selenium compounds for the treatment of infectious diseases. The antimicrobial efficacy of selenium compounds has been tested against a great variety of microorganisms, demonstrating their activity as antibacterial [ 22 ], antifungal [ 23 ], antiviral [ 24 ] and antiparasitic agents [ 25 ]. Ebselen ( 1 ) is the most well-known and well-studied seleno-derivative, especially for its antioxidant effects, GPx-like activity [ 26 ] and antimicrobial activity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as the NC domain is a highly conserved region [372], it represents an ideal target to develop compounds inhibiting HIV-1 and, more specifically, viral assembly. Several inhibitors have been studied over the past few years and their potential therapeutic effects against HIV-1 have been recently reviewed [373,374]. Targeting the late phase of the HIV-1 cell cycle and especially the Gag-cellular proteins interactome represents a promising challenge for the development of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There are two methods of NCp inhibition: one is to compete with the nucleic acid binding site, the other is to interfere directly with the zinc finger structure via zinc ejection. Both approaches have shown promise; however, we chose to use the permanent irreversible ejection of the structural Zn 2+ ion from the viral protein.…”
Section: Figurementioning
confidence: 99%
“…[16][17][18] The NCp is an attractive drug target, as it has been demonstratedt ob emutation resistant,a nd inhibition leads to noninfectious virions. [19] There are two methods of NCp inhibition:o ne is to compete with the nucleic acid binding site, [20,21] the other is to interfere directly with the zinc finger structure via zinc ejection. Both approachesh ave shown promise; however,w ec hose to use the permanent irreversible ejection of the structural Zn 2 + ion from the viral protein.…”
mentioning
confidence: 99%